2013
DOI: 10.1089/bfm.2012.0105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breastfeeding on Head Circumference of Children from Impoverished Communities

Abstract: Objective: This study investigated the effect of exclusive breastfeeding on head circumference (HC) among children living in impoverished communities. Subjects and Methods: A cross-sectional study was conducted among children 12-60 months old from the 39 quilombos located in the State of Alagoas, Brazil. HC deficit was defined by a z-score of less than -2 from the median (based on the 2006 World Health Organization growth standards). Prevalence ratio and 95% confidence interval (95% CI) were estimated using Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
12
0
5
Order By: Relevance
“…Weight-for-length (WLZ) and length-for-age (LAZ) Z scores are equally important beyond the first year of life; stunting in early childhood has been shown to predict future risk of morbidity and mortality (32, 56) although is unlikely in the first 90 days post-partum. Similarly, head-circumference-for-age Z score (HAZ) is thought to be a good indicator of more chronic poor growth and undernutrition (5759). Other potential growth outcomes to be measured include body composition factors (e.g., lean and fat mass, skinfold thickness), currently being explored particularly in BM hormone and obesity studies (11, 13, 41, 60).…”
Section: Discussionmentioning
confidence: 99%
“…Weight-for-length (WLZ) and length-for-age (LAZ) Z scores are equally important beyond the first year of life; stunting in early childhood has been shown to predict future risk of morbidity and mortality (32, 56) although is unlikely in the first 90 days post-partum. Similarly, head-circumference-for-age Z score (HAZ) is thought to be a good indicator of more chronic poor growth and undernutrition (5759). Other potential growth outcomes to be measured include body composition factors (e.g., lean and fat mass, skinfold thickness), currently being explored particularly in BM hormone and obesity studies (11, 13, 41, 60).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the duration and exclusiveness of breastfeeding appear to be positively correlated with IQ and academic achievement (7,9). Clinical studies have revealed that breastfeeding is associated with larger head circumference and brain volume, smaller ventricular volume, larger gangliothalamic ovoid diameters and cortical thickness (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Assim, as ações de promoção dessa prática devem ser implementadas, pois o aleitamento materno exclusivo até os seis meses de vida está associado às boas condições gerais de saúde e nutrição das crianças. 8 Outra importante conquista observada na comunidade foi a redução em 51,9% na prevalência de anemia entre as crianças. A prevalência alcançada em 2012 (20,0%) situou-se bem abaixo daquela encontrada para as crianças investigadas por ocasião do Inquérito Quilombola de Alagoas (52,7%), 6 bem como das crianças do Estado de Alagoas como um todo (45,0%).…”
Section: Discussionunclassified
“…Detalhes sobre o estudo foram descritos em publicações anteriores. [6][7][8] As informações socioeconômicas, demográficas, antropométricas e relativas à saúde foram coletadas por meio de visitas domiciliares e utilizando questionário pré-testado em estudo piloto. No presente estudo, eram elegíveis as mulheres de 18 a 59,9 anos, designadas como "donas de casa" e todas as crianças menores de cinco anos.…”
Section: Métodosunclassified